2018
DOI: 10.1021/acssuschemeng.7b03216
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Nonsteroidal Anti-Inflammatory Drugs from Wastes Using Ionic-Liquid-Based Three-Phase Partitioning Systems

Abstract: Aiming at outlining new strategies for the valorization of solid pharmaceutical wastes as viable alternatives to incineration, this work proposes the use of ionic liquids-based three phase partitioning (IL-based TPP) systems. Ibuprofen, naproxen, and ketoprofen, all belonging to the class of nonsteroidal anti-inflammatory drugs (NSAIDs), were adopted as model compounds. An integrated process has been conceptualized based on three steps: (1) extraction and purification of NSAIDs using the IL-based TPP systems, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…Ionic liquid‐based three phase partitioning (ILTPP) has been investigated because it combines the advantages of the IL‐ATPS and TPP for the concentration and recovery of different molecules including proteins . ILTPP is capable of inducing the formation of a dense and stable protein layer in the middle with IL‐ATPS phase‐forming components.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionic liquid‐based three phase partitioning (ILTPP) has been investigated because it combines the advantages of the IL‐ATPS and TPP for the concentration and recovery of different molecules including proteins . ILTPP is capable of inducing the formation of a dense and stable protein layer in the middle with IL‐ATPS phase‐forming components.…”
Section: Resultsmentioning
confidence: 99%
“…Ionic liquid-based three phase partitioning (ILTPP) has been investigated because it combines the advantages of the IL-ATPS and TPP for the concentration and recovery of different molecules including proteins. [48][49][50] ILTPP is capable of inducing the formation of a dense and stable protein layer in the middle with IL-ATPS phase-forming components. Alvarez-Guerra and Irabien 51 suggested that the salt concentration has the greatest influence on the amount of lactoferrin recovered at the interface.…”
Section: Protein Partitioning In Atpssmentioning
confidence: 99%
“…In order to solve the problem, some scientists have suggested that it is of great value to replace the widely used toxic organic solvents by safely, biodegradable, and environmentally friendly neoteric solvents for the development of sustainable pharmaceutical processes . Ionic liquids (ILs) as neoteric solvents, with the advanced characteristics of non‐volatility, non‐flammability, and high recyclability, have been proposed as green solvents for the extraction, separation, crystallization, and purification of drugs . Particularly, existing experimental data showed that most of imidazolium‐based ILs were considered to be a biodegradable IL and to exhibit quite a low toxicity on human body, which made them even as the component of the active pharmaceutical ingredients (APIs) .…”
Section: Introductionmentioning
confidence: 99%
“…These studied ILs include 1‐ethyl‐3‐methylimidazolium ([Emim] + ), 1‐butyl‐3‐methylimidazolium ([Bmim] + ), and 1‐hexyl‐3‐methylimidazolium ([Hmim] + ) cations paired with tetrafluoroborate ([BF 4 ] − ), hexafluorophosphate ([PF 6 ] − ), trifluoromethanesulfonate ([TfO] − ), and acetate ([AcO] − ) anions. They are known to be highly effective in dissolving nonsteroidal anti‐inflammatory drugs, for example, ibuprofen, which are environmentally friendly and widely available commercially . Herein, we first explore the nature of the first solvation structural shell of ibuprofen and find that its structure is mainly determined by the interactions of anions or cations with ibuprofen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation